2022
DOI: 10.3389/fmicb.2022.927883
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dietary supplements targeting gut microbiota in the prevention and treatment of gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is a kind of metabolic disease occurring during gestation period, which often leads to adverse pregnancy outcomes and seriously harms the health of mothers and infants. The pathogenesis of GDM may be bound up with the abnormal gut microbiota composition in pregnant women. Previous studies have clarified that dietary supplements can regulate the gut microbiota to play a role. Therefore, using dietary supplements, such as probiotics, prebiotics, and synbiotics to target the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Previous findings indicated that probiotics intake promoted to decrease in fasting blood glucose in patients with type 2 Diabetes Mellites (T2DM) ( 35 ). Probably, probiotics contain multiple different microbial species that may affect the progress of sugar digestion and absorption, incretin secretion, and fat absorption ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings indicated that probiotics intake promoted to decrease in fasting blood glucose in patients with type 2 Diabetes Mellites (T2DM) ( 35 ). Probably, probiotics contain multiple different microbial species that may affect the progress of sugar digestion and absorption, incretin secretion, and fat absorption ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This imbalance has the potential to lead to serious gastrointestinal infections, diarrhea, and colon inflammation [ 195 , 196 , 197 ]. In addition, it can have detrimental effects that go beyond the gastrointestinal tract and lead to extraintestinal disorders such as autism, diabetes, obesity, and non-alcoholic fatty liver disease (NAFLD) [ 198 , 199 , 200 ]. Gut microbial dysbiosis is recognized as a growing contributor to the development of several diseases due to its systemic consequences [ 201 ].…”
Section: Mechanisms Of Polysaccharides In Heavy Metal Protectionmentioning
confidence: 99%
“…The higher bacterial richness detected in GDM patients is also correlated with metabolic and inflammatory indicators (3). Some clinical trials suggested that intervention with dietary supplements during pregnancy may have different benefits for pregnant women (4). Some probiotics containing Lactobacillus or Bifidobacterium reduced the incidence of GDM to a certain extent (5).…”
Section: Introductionmentioning
confidence: 99%